Fear and anxiety related to COVID-19 pandemic may predispose to perinatal depression in Italy - Orsolini, Laura; Pompili, Simone; Mauro, Antonella; Salvi, Virginio; Volpe, Umberto (Frontiers in Psychiatry, 2022)
The COVID-19 pandemic situation significantly affected the mental health of the general and clinical population. However, few studies investigated which COVID-19-related psychopathological determinants may predispose to perinatal depression. We evaluated the impact of COVID-19 related anxiety and fear on perinatal depression in Italy. We retrospectively screened 184 perinatal outpatients afferent to Perinatal Mental Health outpatient service, during March 2020-March 2021, by administering the Edinburgh Postnatal Depression Scale (EPDS), the Fear of COVID-19 (FCV-19-S) and the Coronavirus Anxiety Scale (CAS). Among these, 85 patients agreed to be recruited in the present study. The mean EPDS score was 9.0, experiencing a clinically relevant perinatal depression in 45.7% of the sample. The mean FCV-19-S score was 15.0 and CAS was 1.7. Linear regression analyses demonstrated that FCV-19-S and CAS scores statistically significantly predicted EPDS total scores. A positive significant correlation was reported between FCV-19-S and EPDS and between CAS and EPDS. During the COVID-19 pandemic, women in their perinatal period, independently of previous psychiatric history, experienced increased levels of anxiety, fear and psychological distress, due to subsequent isolation, quarantine, lockdown and deprivation of their normal social support. Further preventive and screening strategies should be implemented in order to early identify at-risk pregnant and puerperal women during the COVID-19 pandemic.